Experimental Study on a Novel Optimal Differential Pressure Reset Method for Online Application in Chilled Water System. (2015) - Zhao, Tianyi; Ma, Liangdong; Zhang, Jili
Abstract: This paper firstly define most unfavorable thermodynamic loop to reflect the dynamic situation of terminal cooling load distribution, then present its online identification method that can easily applied for optimal reset of differential pressure. We use the optimal domain of maximum valve position among whole braches in chilled water system to calculate the variation of differential pressure setpoint, and control the pumps according to the optimal setpoint. We applied presented method to a VWF retrofit project in a Suzhou factory building and evaluate its energy saving effect through its equipped building energy management system. Experimental results showed that presented method can achieve 22%-53% pump power consumption savings compared to traditional control method. During the test period, the average level of valve position of presented method was highest among all tested control strategies. The optimal reset method of differential pressure presented in this paper is an energy efficient, high stability and easily online applied control method.